Examine the relationship between usage of IT devices and the quality of courier service- Field study on DHL Express and Logistics Syria customers - Zyoud, Nourah Mofeed (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The aim of this research is to study the relationship between the use of IT equipment and the quality of service in DHL Company in Syria through its relationship with the dimensions of service quality (tangibility, reliability, responsiveness, warranty, care). In the Syrian Arab Republic, it relied on the questionnaire as a tool for the study, where it collected its primary data through 57 questionnaires, and used the linear correlation method to study the relationship between the independent variable and the dependent. The study found that there is a direct and strong relationship between the independent variable (IT hardware) and the dimensions of the dependent variable (reliability, tangibility, responsiveness, warranty, and care) from the point of view of the research sample. هدف هذا البحث إلى دراسة العلاقة بين استخدام أجهزة تكنولوجيا المعلومات وجودة الخدمة في شركة DHL في سورية من خلال علاقتها مع أبعاد جود الخدمة (الملموسية، الاعتمادية، الاستجابة، الضمان، العناية)، وقد اعتمدت الباحثة على أسلوب العينة القصدية من خلال استهدافها لعملاء الشركة حصراً في الجمهورية العربية السورية، واعتمدت على الاستبانة كأداة للدراسة، حيث قامت بجمع بياناتها الأولية من خلال 57 استبانة، واستخدمت أسلوب الارتباط الخطي لدراسة العلاقة بين كل من المتغير المستقل والتابع. توصلت الدراسة إلى وجود علاقة طردية وقوية بين المتغير المستقل (أجهزة تكنولوجيا المعلومات) وأبعاد المتغير التابع (كل من الاعتمادية والملموسية، والاستجابة، والضمان، والعناية) من وجهة نظر عينة البحث.